A study on the factors influencing housing purchase decision nearby airport - Liew, Qian Ni (2022)
Living near an airport is a chance and choice by the people. It because of the location, view, budget, and others. However, owning a house near an airport can expose to some negative impacts. Thus, this research was conducted to study on the factors influencing housing purchase decision nearby airport, the preferences, and the impacts. Questionnaires were used to collect data with total respondents of 100 in Klang Valley area and analysed using descriptive analysis and relative important index. The results obtained shows that there are six factors influencing housing purchase decision which were price, financial status, type of houses, neighbourhood, developer reputation, and house structure. However, space was the most factors considered followed with neighbourhood and type of house. Besides, the serious impact of housing purchase nearby airport was noise pollution. Thus, the developer and related agencies may consider on these factors and impact when planning to carry out property development nearby airport. Furthermore, future researchers suggested to conduct the same study but in different states such as Penang and Sarawak, so can have a better comparison and improvement. Moreover, it also provided a better understanding when people consider buying their house.